2017
DOI: 10.1523/jneurosci.2024-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Target Cell Type-Dependent Differences in Ca2+Channel Function Underlie Distinct Release Probabilities at Hippocampal Glutamatergic Terminals

Abstract: Target cell type-dependent differences in presynaptic release probability (P r ) and short-term plasticity are intriguing features of cortical microcircuits that increase the computational power of neuronal networks. Here, we tested the hypothesis that different voltage-gated Ca 2ϩ channel densities in presynaptic active zones (AZs) underlie different P r values. Two-photon Ca 2ϩ imaging, triple immunofluorescent labeling, and 3D electron microscopic (EM) reconstruction of rat CA3 pyramidal cell axon terminals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 56 publications
4
73
2
Order By: Relevance
“…Similar results were obtained using the low affinity Ca 2+ indicator OGB-5N (Figure 1F). The larger average sAPCaT in SC boutons contrasts previous reports that sAPCaT amplitudes predict synaptic strength (Eltes et al, 2017; Holderith et al, 2012; Koester and Johnston, 2005).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Similar results were obtained using the low affinity Ca 2+ indicator OGB-5N (Figure 1F). The larger average sAPCaT in SC boutons contrasts previous reports that sAPCaT amplitudes predict synaptic strength (Eltes et al, 2017; Holderith et al, 2012; Koester and Johnston, 2005).…”
Section: Resultscontrasting
confidence: 99%
“…Previous analysis of gold particle labelling of Cav2.1 channels in CNS synapses suggested that VGCCs form clusters (Eltes et al, 2017; Holderith et al, 2012, Nakamura et al, 2015; Miki et al, 2017). We therefore performed a spatial point pattern analysis that test for deviations in the density of particles over various spatial scales, using the Ripley’s H-function, an analysis method that is particularly sensitive to particle clustering (down to two points per cluster, for observed NNDs; Figure S3A-C).…”
Section: Resultsmentioning
confidence: 99%
“…Significant differences in Ca 2+ influx arising from local differences in the function or subunit composition of Ca 2+ channels at different hippocampal synapses have also been observed (Éltes et al, 2017). Voltage dependence might also vary at different synapses as a consequence of local differences in the ionic environment and neuromodulatory influence.…”
Section: Introductionmentioning
confidence: 98%
“…; Eltes et al . ). To normalize data across batches of dyes, G max / R values were measured by imaging a sealed (tip melted and closed by heating) pipette filled with intracellular solution containing 10 mM CaCl 2 for each cell.…”
Section: Methodsmentioning
confidence: 97%
“…For the measurement of variability in unitary peak [Ca 2+ ] transient amplitudes, data were collected from the following 5 min. AP-evoked changes in fluorescence were quantified as G/R(t) = (F green(t) -F rest, green )/(F red -I dark, red ) where F green(t) represents the green fluorescence signal as a function of time, F rest, green is the green fluorescence before stimulation, and I dark, red is the dark current in the red channel (Holderith et al 2012;Eltes et al 2017). To normalize data across batches of dyes, G max /R values were measured by imaging a sealed (tip melted and closed by heating) pipette filled with intracellular solution containing 10 mM CaCl 2 for each cell.…”
Section: In Vitro Two-photon Ca 2+ Imaging and Data Analysismentioning
confidence: 99%